(untitled) (Journal of Advanced Research in Social Sciences, 2023)
The recognition of lived experience as an invaluable resource for reform and program development in criminal justice has seen a positive shift in recent years. Unexamined, or at least unarticulated, is the value that this inclusion of lived experience could have in efforts toward desistance. This article suggests the Inside Out Prison Exchange Program and the associated prison and community-based Think Tanks established in Victoria, Australia, can be more than a place for advocacy, but indeed a motivator for desistance among participants. Through a discussion of desistance theory, this paper outlines how these programs can promote desistance efforts as a result of their voluntary nature and continuity during and after incarceration. In these spaces, incarcerated individuals are given opportunities to engage with community members, contribute in prosocial capacities, and gain significant knowledge and skills surrounding criminal justice reform. This meaningful educational environment is one which can foster self-determination, non-offender identity development, and community connection, all of which are significant factors in the journey of desistance.